Preparation method of wear-regenerative super-hydrophobic durable anti-corrosion coating
By using nanoparticles and fluoro-containing silane coupling agent in the superhydrophobic coating, combining low-surface energy polymers and oily binders, a wear-regenerating superhydrophobic durable corrosion-resistant coating with a self-similar structure is solved, and the existing coating cannot recover chemical erosion and cannot repel salt spray, achieving the mechanical stability and efficient corrosion-proof performance of the coating.
Patent Information
- Application Number
- CN202411660348.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing superhydrophobic coating cannot restore the superhydrophobicity that is chemically eroded, and micropore defects cannot repel corrosive media in molecular/ionic states such as salt spray.
Nanoparticles and fluoro-containing silane coupling agent are dispersed in the ethanol solution, and low-surface energy polymer and oily binder are added, formed by ultrasonic stirring and phase separation emulsion, sprayed on the surface of the metal substrate to form a self-similar superhydrophobic coating with a thickness of 10 to 100 μm, and a uniform dispersion of low-surface energy nanoparticles and high-hardness oily binder is sprayed on the surface to form an abrasive regenerated superhydrophobic durable anti-corrosion coating with a thickness of 20 to 100 μm.
The mechanical stability and wear regeneration ability of the superhydrophobic coating are achieved, and the superhydrophobicity can be restored after chemical erosion and mechanical wear, and the barrier properties to corrosive media are significantly improved.
Smart Images

Figure CN119500522A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating materials and relates to a method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating. Background Art
[0002] In recent years, the bionic super-hydrophobic surface (contact angle CA greater than 150°, sliding angle SA less than 10°) inspired by nature has attracted widespread attention from researchers due to its excellent hydrophobic properties. The surface of super-hydrophobic materials has two significant characteristics: micro- / nanoscale roughness and low surface energy. It has broad application prospects in self-cleaning, concrete protection, oil-water separation, anti-icing, anti-corrosion, biomedicine and other fields; especially in the field of metal corrosion protection, super-hydrophobic coatings are highly repellent to aqueous media, thereby reducing the contact area and contact time between them, and are considered to be the most promising coating for achieving long-term protection of metals.
[0003] At present, the construction of super-hydrophobic coatings includes two ways: constructing a rough structure with a low surface energy material, or first preparing a rough structure and then modifying it with a low surface energy material; in order to obtain a high roughness surface, people have proposed many technologies. CN114717544A discloses a method for preparing a durable super-hydrophobic coating for metal corrosion protection, in which the metal substrate is first subjected to surface phosphating treatment with a calcium-phosphorus plating solution with dispersed carbon quantum dots, and then a fluorine-containing silica sol containing rubber micropowder is pulled and coated, thereby forming a durable anti-corrosion, super-hydrophobic coating on the metal surface; CN114773921A discloses a method for quickly preparing a stable super-hydrophobic surface on a complex shape, in which a non-solvent is added to a solution containing a binder and fluorinated nanoparticles to induce phase separation, thereby obtaining a uniform super-hydrophobic emulsion, and preparing a stable super-hydrophobic coating by dip coating. Although the super-hydrophobic coating prepared by this method has good anti-corrosion performance in an aqueous medium, corrosive ions, molecules and particles in the air can easily penetrate into the porous coating, causing serious corrosion to the metal alloy.
[0004] More importantly, the existing preparation method usually sprays low surface energy materials on the surface of traditional coatings to achieve super hydrophobicity and high barrier properties of the coating. CN108441085A discloses a method for preparing a water-based super-amphiphobic long-lasting anticorrosion coating. The method uses a water-based epoxy resin as a base layer and sprays a super-amphiphobic surface layer composed of a fluorinated organosilicon polymer, fluorinated silane-modified nanoparticles and a fluorocarbon surfactant on its surface. The super-amphiphobic surface layer exhibits excellent corrosion resistance, super-amphiphobicity and mechanical stability. Although this method improves the barrier property of the coating to corrosive media in the air, due to the non-uniformity of the bulk phase, when the super-amphiphobic surface layer is chemically eroded or mechanically worn, the coating becomes hydrophilic; therefore, it is very necessary to develop a long-lasting anticorrosion coating with bulk consistency suitable for high temperature, high salt and high humidity environments, which is of great significance for the practical application of super-hydrophobic coatings. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating, overcome the shortcomings of the prior art, and solve the problems that the existing super-hydrophobic coating cannot restore the super-hydrophobicity that has been chemically eroded and the micropore defects cannot repel corrosive media in molecular / ionic states such as salt spray.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating, specifically comprising the following steps:
[0008] 1) The nanoparticles are dispersed in an ethanol solution, ammonia water is added to make the solution alkaline, and then ultrasonic stirring is continued for 1 to 2 hours, and then a fluorinated silane coupling agent and tetraethyl orthosilicate are added. Stirring is continued at room temperature for 2 to 4 hours and then centrifuged. The obtained solid is washed with ethanol and an organic solvent, and then dispersed in an organic solvent to obtain a low surface energy nanoparticle dispersion.
[0009] 2) Add the low surface energy polymer to the organic solvent and stir until it becomes viscous, add the mixed solution of the oily binder and the non-polar solvent, continue stirring for 1 to 3 hours, slowly add the alcohol solvent under rapid stirring to induce the oily binder to phase separate, then add the low surface energy nanoparticle dispersion of step 1) and continue stirring for 1 hour and then ultrasonicate for 20 minutes to obtain a uniform super hydrophobic emulsion. Spray the obtained super hydrophobic emulsion on the surface of the metal substrate and cure it at room temperature for 6 to 24 hours to obtain a self-similar super hydrophobic coating with a thickness of 10 to 100 μm;
[0010] 3) The organic solvent and the high-hardness oily binder are mixed and stirred, and the low-surface-energy nanoparticle dispersion of step 1) is added and stirred for 0.5 to 2 hours, and then ultrasonicated for 5 to 30 minutes to obtain a uniform dispersion of low-surface-energy nanoparticles and high-hardness oily binder, which is then sprayed onto the surface of the self-similar super-hydrophobic coating of step 2) at room temperature. After curing at room temperature for 12 to 24 hours, a wear-regenerated super-hydrophobic durable anti-corrosion coating with a thickness of 20 to 100 μm is obtained.
[0011] Preferably, the nanoparticles are any one or a mixture of two or more of graphene oxide, carbon nanotubes, silicon carbide, titanium carbide nanosheets, vermiculite, hexagonal boron nitride, zirconium oxide, aluminum oxide, silicon dioxide and titanium dioxide, and the mass ratio of the nanoparticles to the non-polar solvent in the dispersion is 1:1 to 10:1.
[0012] Preferably, in step 1), the fluorinated silane coupling agent is any one of perfluorodecyltriethoxysilane, perfluorodecyltrimethoxysilane or perfluorooctyltriethoxysilane, or a mixture of two or more thereof, the amount of the fluorinated silane coupling agent added is 0.2% to 1% of the total volume of the solution before centrifugation, and the ratio of the fluorinated silane coupling agent to tetraethyl orthosilicate added is 1:1 to 5:1.
[0013] Preferably, the organic solvent is any one of toluene, xylene, ethylene dichloride, acetone, methyl formate, ethyl acetate, butyl acetate and dimethyl carbonate, or a mixture of two or more thereof.
[0014] Preferably, in step 2), the low surface energy high molecular polymer is any one of silica gel, fluororubber, high density polyethylene, polytetrafluoroethylene, polypropylene, polyvinylidene fluoride and polyperfluoroethylene propylene, or a mixture of two or more thereof, and the mass fraction of the low surface energy high molecular polymer in the super hydrophobic emulsion is 5% to 10%.
[0015] Preferably, in step 2), the oily binder is any one of polyvinylidene fluoride, polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene, silicone-modified polyurethane and epoxy resin, or a mixture of any two or more thereof, and the added amount ratio of the oily binder to the non-polar solvent is 1:10 to 1:1.
[0016] Preferably, in step 2), the alcohol solvent is any one of methanol, ethanol, isopropanol, n-propanol and n-butanol, or a mixture of any two or more thereof, and the added ratio of the alcohol solvent to the organic solvent is 1:5 to 1:1.
[0017] Preferably, in step 2), the mass ratio of the low surface energy nanoparticles to the oily binder in the superhydrophobic emulsion is 1:2 to 3:1.
[0018] Preferably, the high hardness oily binder in step 3) is any one of phenolic resin, polyurethane resin, silicone-modified polyester resin, epoxy resin, bisphenol A epoxy acrylate and polyester polyurethane resin, or a mixture of any two or more thereof.
[0019] Preferably, in step 3), the mass ratio of the low surface energy nanoparticles to the high hardness binder is 1:20 to 1:5.
[0020] Beneficial Effects
[0021] 1. Wettability and mechanical stability of superhydrophobic coatings
[0022] The super-hydrophobic coating prepared by the present invention has excellent mechanical stability. After being polished with 800-mesh sandpaper for 6 cycles (each cycle is 0.5 m) under a load of 200 g, the water contact angle is greater than 155° and the sliding angle is less than 4°. After polishing for 80 cycles, the water contact angle is greater than 155° and the sliding angle is less than 5°.
[0023] 2. Mechanical wear regeneration of superhydrophobicity
[0024] The super-hydrophobic coating prepared by the present invention can restore the super-hydrophobicity of the surface eroded by strong acid and strong alkali solutions, such as Figure 2 As shown, after being immersed in 1 mol hydrochloric acid or 1 mol sodium hydroxide solution until the surface fails, the hydrophobicity is restored after being polished with 800-grit sandpaper for 2.0 m under a load of 200 g, the water contact angle is greater than 155°, and the sliding angle is less than 4°. In particular, the effect of mechanical wear regeneration can be achieved for multiple cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a process diagram of the preparation method of the wear-regenerated super-hydrophobic durable anti-corrosion coating of the present invention;
[0026] Figure 2 It is a schematic diagram of the acid and alkali resistance experiment and the wear regeneration superhydrophobicity of Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Generally, the components of the embodiments of the present invention described and shown in the embodiments herein can be arranged and designed in various different configurations.
[0028] Therefore, the following detailed description of the embodiments of the present invention provided in the embodiments is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0030] Example 1
[0031] 1) In this embodiment, 2.0 g of nano hexagonal boron nitride was added to 92 ml of ethanol solution and ultrasonically stirred for dispersion, and then 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 0.4 ml of perfluorodecyltriethoxysilane and 0.2 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the mixture was centrifuged and washed with ethanol and ethyl acetate several times, and then dispersed in 5.0 ml of ethyl acetate to obtain a low surface energy nano hexagonal boron nitride dispersion.
[0032] 2) 1.0g polytetrafluoroethylene micropowder is added to 3.0g ethyl acetate and stirred until viscous, 5.5g mass ratio is added to polystyrene-block-poly (ethylene-ran-butylene)-block-polystyrene / ethyl acetate mixed solution of 1:5, and after continuing to stir for 1h, 3.0ml absolute ethanol is slowly added under rapid stirring to form a phase separation emulsion, and then 7.0g step 1) dispersion liquid is added to continue stirring for 1h and ultrasonic 20min to obtain a phase separation super hydrophobic emulsion. The obtained phase separation super hydrophobic emulsion is sprayed on the Q235 surface, cured at room temperature for 24h, and a super hydrophobic coating with a self-similar structure is obtained.
[0033] 3) Ethyl acetate and silicone polyester resin are mixed and stirred, 7.0 g of ethyl acetate dispersion of low surface energy nano zirconium oxide is added, stirring is continued for 1 hour, and then ultrasonicated for 20 minutes to obtain a uniform dispersion of low surface energy nano zirconium oxide and silicone polyester resin, which is then sprayed onto the surface of the super hydrophobic coating in step 2) at room temperature. After curing at room temperature for 12 to 24 hours, a wear-regenerated super hydrophobic durable anti-corrosion coating is obtained.
[0034] Example 2
[0035] 1) In this embodiment, 2.1 g of titanium carbide nanosheets were added to 92 ml of ethanol solution and ultrasonically stirred for dispersion, and then 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 1.0 ml of perfluorodecyltrimethoxysilane and 0.25 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the solution was centrifuged and washed with ethanol and toluene several times, and then dispersed in 5.0 ml of toluene to obtain a low surface energy modified titanium carbide nanosheet dispersion.
[0036] 2) 2.0g polyvinylidene fluoride micropowder is added to 3.0g toluene and stirred until viscous, 5.5g of polyvinylidene fluoride / toluene mixed solution with a mass ratio of 1:5 is added, and after continuing to stir for 1h, 3.0ml methanol is slowly added under rapid stirring to form a phase separation emulsion, and then 7.5g of the dispersion of step 1) is added and continued to stir for 1h and then ultrasonicated for 20min to obtain a phase separation super hydrophobic emulsion. The obtained phase separation super hydrophobic emulsion is sprayed on the surface of Q235 and cured at room temperature for 24h to obtain a super hydrophobic coating with a self-similar structure.
[0037] 3) 4.0 g of toluene and 10.0 g of silicone polyester resin were mixed and stirred, 7.5 g of toluene dispersion of low surface energy nano-alumina was added, stirring was continued for 1 hour, and then ultrasonicated for 20 minutes to obtain a uniform dispersion of low surface energy nano-alumina and silicone polyester resin, which was then sprayed onto the surface of the super-hydrophobic coating in step 2) at room temperature. After curing at room temperature for 24 hours, a wear-regenerated super-hydrophobic durable anti-corrosion coating was obtained.
[0038] Example 3
[0039] 1) In this embodiment, 2.1 g of graphene oxide was added to 92 ml of ethanol solution and ultrasonically stirred for dispersion, and then 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 0.5 ml of perfluorooctyltriethoxysilane and 0.5 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the mixture was centrifuged and washed with ethanol and acetone several times, and then dispersed in 5.0 ml of acetone to obtain a low surface energy nano hexagonal boron nitride dispersion.
[0040] 2) 1g polyperfluoroethylene propylene powder is added to 3.0g acetone and stirred until viscous, 5.5g mass ratio is added to the organosilicon-modified polyurethane / acetone mixed solution of 1:5, and after continuing to stir for 1h, 3.0ml isopropanol is slowly added under rapid stirring to form a phase separation emulsion, and then 7.5g step 1) dispersion liquid is added to continue stirring for 1h and ultrasonic 20min to obtain a phase separation super hydrophobic emulsion. The obtained phase separation super hydrophobic emulsion is sprayed on the Q235 surface and cured at room temperature for 24h to obtain a super hydrophobic coating with a self-similar structure.
[0041] 3) 2.0 g of acetone and 10.0 g of epoxy resin were mixed and stirred, 7.5 g of the acetone dispersion of low surface energy nano-silica in step 1 was added, stirring was continued for 2 h, and then ultrasonicated for 20 min to obtain a uniform dispersion of low surface energy nano-silica and epoxy resin, which was then sprayed onto the surface of the super-hydrophobic coating in step 2) at room temperature. After curing at room temperature for 12 h, a wear-regenerated super-hydrophobic durable anti-corrosion coating was obtained.
[0042] Example 4
[0043] 1) In this embodiment, 3.0 g of vermiculite was added to 92 ml of ethanol solution and dispersed by ultrasonic stirring. Then, 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 1.5 ml of perfluorodecyltriethoxysilane and 0.5 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the solution was centrifuged and washed with ethanol and dichloroethane several times, and then dispersed in 5.0 ml of dichloroethane to obtain a low surface energy vermiculite dispersion.
[0044] 2) 1g high density polyethylene micropowder is added in 3.0g ethylene dichloride and stirred until viscous, 5.5g mass ratio is added to epoxy resin / ethylene dichloride mixed solution of 1:5, after continuing to stir for 1h, 3.0ml n-butanol is slowly added under rapid stirring to form a phase separation emulsion, then 7.5g step 1) dispersion liquid is added to continue stirring for 1h and ultrasonic 20min is obtained to obtain a phase separation super hydrophobic emulsion. The phase separation super hydrophobic emulsion obtained is sprayed on Q235 surface, cured at room temperature for 24h, and a super hydrophobic coating with a self-similar structure is obtained.
[0045] 3) 5.0 g of ethylene dichloride and 10.0 g of polyester polyurethane resin were mixed and stirred, 7.5 g of ethylene dichloride dispersion of low surface energy nano zirconium oxide was added, stirring was continued for 2 h, and then ultrasonicated for 20 min to obtain a uniform dispersion of low surface energy nano zirconium oxide and polyester polyurethane resin, which was then sprayed onto the surface of the super hydrophobic coating in step 2) at room temperature. After curing at room temperature for 16 h, a wear-regenerated super hydrophobic durable anti-corrosion coating was obtained.
[0046] Comparative Example 1
[0047] 1) In this comparative example, 2.0 g of titanium carbide nanosheets were added to 92 ml of ethanol solution and ultrasonically stirred for dispersion, and then 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 0.4 ml of perfluorodecyltriethoxysilane and 0.2 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the mixture was centrifuged and washed with ethanol and acetone several times, and then dispersed in 5.0 ml of acetone to obtain a low surface energy nano hexagonal boron nitride dispersion.
[0048] 2) 1.0g polyvinylidene fluoride powder is added to 3.0g acetone and stirred until viscous, 5.5g mass ratio of polystyrene-block-poly (ethylene-ran-butylene)-block-polystyrene / acetone mixed solution is added, and stirring is continued for 1h, and 3.0ml of anhydrous ethanol is slowly added under rapid stirring to form a phase separation emulsion, and then 7.0g step 1) dispersion is added and stirred for 1h and then ultrasonicated for 20min to obtain a phase separation super hydrophobic emulsion. The obtained phase separation super hydrophobic emulsion is sprayed on the surface of Q235 and cured at room temperature for 24h to obtain a super hydrophobic coating with a self-similar structure;
[0049] Comparative Example 2
[0050] 1) In this embodiment, 2.0 g of nano hexagonal boron nitride was added to 92 ml of ethanol solution and ultrasonically stirred for dispersion, and then 8 ml of ammonia water was added to adjust the pH of the solution. After ultrasonic stirring for 2 h, 0.4 ml of perfluorodecyltriethoxysilane and 0.2 ml of tetraethyl orthosilicate were added. After stirring at room temperature for 2 h, the mixture was centrifuged and washed with ethanol and ethyl acetate several times, and then dispersed in 5.0 ml of ethyl acetate to obtain a low surface energy nano hexagonal boron nitride dispersion.
[0051] 2) 1.0g polytetrafluoroethylene powder is added to 3.0g ethyl acetate and stirred until viscous, 5.5g mass ratio is 1:5 polystyrene-block-poly (ethylene-ran-butylene)-block-polystyrene / ethyl acetate mixed solution is added, and after continuing to stir for 1h, 7.0g step 1) dispersion liquid is added and continued to stir for 1h and then ultrasonicated for 20min to obtain a super hydrophobic emulsion. The obtained phase separation super hydrophobic emulsion is sprayed on the Q235 surface and cured at room temperature for 24h to obtain a super hydrophobic coating.
[0052] 3) Ethyl acetate and silicone polyester resin are mixed and stirred, 7.0 g of the ethyl acetate dispersion of low surface energy nano zirconium oxide in step 1 is added, stirring is continued for 1 hour, and then ultrasonicated for 20 minutes to obtain a uniform dispersion of low surface energy nano zirconium oxide and silicone polyester resin, which is then sprayed onto the surface of the super hydrophobic coating in step 2) at room temperature, and cured at room temperature for 24 hours to obtain a hydrophobic anti-corrosion coating.
[0053] The electrochemical impedance of the composite coatings obtained in Examples 1 to 4 and Comparative Examples 1 to 2 was measured by immersion in 3.5wt% NaCl solution for different time periods according to GB / T10834-2008 standard. The water contact angle (4μL water droplet) of the surface of the coating after 6 cycles and 80 cycles (each cycle is 0.5m) of wear (800 mesh sandpaper) under a load of 200g before immersion was observed.
[0054] Table 1.
[0055]
[0056] As shown in Table 1, by comparison with Comparative Example 1, the good oil absorption of the oily binder enables the self-similar structure of the super-hydrophobic coating to be effectively filled with the composite coating constructed by the silicone-modified polyester resin, forming a protective "armor" structure. Such a micro / nanostructure helps to enhance the mechanical stability of the coating, showing better mechanical stability than the self-similar super-hydrophobic coating constructed by simple phase separation. After 80 cycles of sandpaper wear under a load of 200g, the water contact angle can still be as high as 156.3°, and the sliding angle is 3.6°.
[0057] The super-hydrophobic coating with bulk consistency in Example 1 greatly improves the acid and alkali resistance of the coating. Figure 2 As shown, after soaking in 1M hydrochloric acid for 10 minutes, the hydrophobic angle dropped from 157.2° to 151.3°, and the sliding angle dropped from 6.5° to 12.7°, indicating that obvious chemical erosion occurred on the coating surface, and then after 12 cycles of sandpaper wear test, the water contact angle quickly recovered to 158.2°, and the sliding angle recovered to 2.9°. After 30 minutes of immersion in 1M hydrochloric acid, the water contact angle dropped to 150.1°, and the sliding angle dropped to 23.7°. After 12 cycles of wear again, the water contact angle and the sliding angle quickly recovered to 158.6° and 2.9°. Similarly, after the coating was soaked in 1M sodium hydroxide for 10 minutes, the coating lost its super-hydrophobicity, and after cyclic wear, the super-hydrophobicity can be quickly restored, which fully illustrates that the coating of the present invention has the characteristic of rapidly recovering from the super-hydrophobicity loss caused by chemical erosion. Compared with Comparative Example 2, since the coating in Comparative Example 2 does not have superhydrophobicity, it exhibits a Wenzel state in the solution, and the liquid completely penetrates the rough surface and fully contacts the coating, making the coating unable to exhibit acid and alkali resistance.
[0058] By comparing the anti-corrosion performance of the embodiment and comparative example 2, it is found that when the coating thickness is the same, the durable wear-regenerated super hydrophobic anti-corrosion coating prepared by the method provided in the embodiment of the present application can improve the barrier property of the coating to corrosive media without reducing the hydrophobicity of the coating. After immersion for 20 days, the impedance values in embodiments 1 to 4 are 4 orders of magnitude higher than those in comparative example 2. In embodiments 1 to 4, by changing the nanofiller and the oily binder, the surface wettability and anti-corrosion performance of the composite coatings of different components are almost consistent, which proves the practicality and universality of the present invention.
[0059] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that all other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
Claims
1. A method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating, characterized in that: The specific steps include: 1) The nanoparticles are dispersed in an ethanol solution, and ammonia water is added to make the solution alkaline. After ultrasonic stirring for 1 to 2 hours, a fluorinated silane coupling agent and tetraethyl orthosilicate are added. After stirring at room temperature for 2 to 4 hours, the solution is centrifuged. The obtained solid is washed with ethanol and an organic solvent, and then dispersed in an organic solvent to obtain a low surface energy nanoparticle dispersion. 2) Add a low surface energy polymer to an organic solvent and stir until it becomes viscous, add a mixed solution of an oily binder and a non-polar solvent, continue stirring for 1 to 3 hours, slowly add an alcohol solvent under rapid stirring to induce phase separation of the oily binder, then add the low surface energy nanoparticle dispersion of step 1) and continue stirring for 1 hour and then ultrasonicate for 20 minutes to obtain a uniform superhydrophobic emulsion, spray the obtained superhydrophobic emulsion on the surface of a metal substrate, and cure at room temperature for 6 to 24 hours to obtain a self-similar superhydrophobic coating with a thickness of 10 to 100 μm; 3) The organic solvent and the high hardness oily binder are mixed and stirred, and the low surface energy nanoparticle dispersion of step 1) is added and continued to be stirred for 0.5 to 2 hours, and then ultrasonicated for 5 to 30 minutes to obtain a uniform dispersion of low surface energy nanoparticles and high hardness oily binder, which is then sprayed onto the surface of the self-similar superhydrophobic coating of step 2) at room temperature. After curing at room temperature for 12 to 24 hours, a wear-regenerated superhydrophobic durable anti-corrosion coating with a thickness of 20 to 100 μm is obtained.
2. The method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating according to claim 1, characterized in that: In step 1), the nanoparticles are any one or a mixture of two or more of graphene oxide, carbon nanotubes, silicon carbide, titanium carbide nanosheets, vermiculite, hexagonal boron nitride, zirconium oxide, aluminum oxide, silicon dioxide and titanium dioxide, and the mass ratio of the nanoparticles to the non-polar solvent in the dispersion is 1:1 to 10:
1.
3. The method for preparing a wear-regenerated super-hydrophobic anti-durable corrosion coating according to claim 1, characterized in that: In step 1), the fluorinated silane coupling agent is any one of perfluorodecyltriethoxysilane, perfluorodecyltrimethoxysilane or perfluorooctyltriethoxysilane, or a mixture of two or more thereof, the amount of the fluorinated silane coupling agent added is 0.2% to 1% of the total volume of the solution before centrifugation, and the ratio of the fluorinated silane coupling agent to tetraethyl orthosilicate added is 1:1 to 5:
1.
4. The method for preparing a wear-regenerated super-hydrophobic anti-durable corrosion coating according to claim 1, characterized in that: In step 1), the organic solvent is any one of toluene, xylene, ethylene dichloride, acetone, methyl formate, ethyl acetate, butyl acetate and dimethyl carbonate, or a mixture of two or more thereof.
5. The method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating according to claim 1, characterized in that: In step 2), the low surface energy high molecular polymer is any one of silica gel, fluororubber, high-density polyethylene, polytetrafluoroethylene, polypropylene, polyvinylidene fluoride and polyperfluoroethylene propylene, or a mixture of two or more thereof, and the mass fraction of the low surface energy high molecular polymer in the super hydrophobic emulsion is 5% to 10%.
6. The method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating according to claim 1, characterized in that: In step 2), the oily binder is any one of polyvinylidene fluoride, polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene, silicone-modified polyurethane and epoxy resin, or a mixture of any two or more thereof, and the addition ratio of the oily binder to the non-polar solvent is 1:10 to 1:
1.
7. The method for preparing a wear-regenerated super-hydrophobic durable anti-corrosion coating according to claim 1, characterized in that: In step 2), the alcohol solvent is any one of methanol, ethanol, isopropanol, n-propanol and n-butanol, or a mixture of any two or more thereof, and the added ratio of the alcohol solvent to the organic solvent is 1:5 to 1:
1.
8. The method for preparing a durable wear-regenerated super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In step 2), the mass ratio of the low surface energy nanoparticles to the oily binder in the super hydrophobic emulsion is 1:2 to 3:
1.
9. The method for preparing a durable wear-regenerated super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In step 3), the high-hardness oily binder is any one of phenolic resin, polyurethane resin, silicone-modified polyester resin, epoxy resin, bisphenol A epoxy acrylate and polyester polyurethane resin, or a mixture of any two or more thereof.
10. The method for preparing a durable wear-regenerated super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In step 3), the mass ratio of the low surface energy nanoparticles to the high hardness binder is 1:20 to 1:5.
Citation Information
Patent Citations
Waterborne super-amphiphobic long-effective anticorrosive coating and preparation method thereof
CN108441085A
Preparation method of super-hydrophobic coating with excellent self-repairing and anti-corrosion properties
CN111961411A
Preparation method of weather-resistant 5G antenna housing super-lyophobic self-cleaning coating
CN113308151A
Preparation method of durable photo-thermal real-time self-repairing super-amphiphobic coating
CN113388293A
Method for preparing stable super-hydrophobic surface on complex modeling base material at super-fast speed
CN114773921A
Cited By
Reconfigurable intelligent anti-corrosion coating and preparation method thereof
CN120484618A
High-wear-resistance aluminum-copper alloy material and preparation method thereof
CN120485563A
Processing technology of antibacterial breathable fabric and clothing applying same
CN120486111A
Double-size wear-resistant super-hydrophobic material based on phase separation method as well as preparation method and application of double-size wear-resistant super-hydrophobic material
CN120818263A
A dual-size wear-resistant super-hydrophobic material based on a phase separation method, a preparation method and applications thereof
CN120818263B